Menghadapi era post-truth: Pentingnya literasi media - Wulandari, Aida Olivia Desy Tri (Maliki Interdisciplinary Journal, 2024)
This article discusses the phenomenon of the post-truth era, where objective facts have less influence in shaping public opinion compared to emotions and personal beliefs. This era is characterized by the widespread spread of fake news, misinformation, and conspiracy theories, amplified by social media algorithms and echo chambers. Media literacy is becoming increasingly important as a tool to face these challenges. Media literacy involves the ability to critically access, analyze, evaluate and create media content. This article outlines the challenges in media literacy in the post-truth era, including difficulties distinguishing fact and opinion, content manipulation, and confirmation bias. Additionally, this article offers practical solutions to improve media literacy, such as the integration of media literacy education in school curricula, training for teachers and the general public, public awareness campaigns, and collaboration with social media platforms for fact verification and algorithm transparency. By strengthening media literacy, individuals can become more critical consumers of information and responsible producers of content, helping to build a more informed and democratic society.